Optimized Soluble Expression and Purification of an Aggregation-prone Protein by Fusion Tag Systems and On-column Cleavage in Escherichia coli - Li, Wen; Gao, Mingming; Liu, Wenchao; Kong, Yuelin; Tian, Hong; Yao, Wenbing; Gao, Xiangdong (Protein and Peptide Letters, 2012)
Previously we constructed a fusion protein based on GLP-1 and globular adiponectin but unfortunately its yield was low because it was mainly expressed as inclusion bodies. Herein to optimize the soluble expression of this fusion protein we tried several fusion tag systems. Fusion tags, including GST-, Trx- and MBP-tag, greatly improved the soluble expression of the fusion protein. However, these tag-fusion proteins were aggregation-prone as judged by Native PAGE and gel filtration chromatography, and this aggregation reduced the specificity of enterokinase-mediated enzyme cleavage which was essential to remove the fusion tags. To improve the specificity of protein cleavage, we employed on-column cleavage for downstream purification. Finally using optimized expression followed by on-column cleavage, we obtained the product fusion protein with a yield of 1.2 mg per g wet bacterial cells which was 8-fold higher than before. This method improved the yield and simplified the process, and as a convenient method it can also be used for the preparation of other aggregation-prone proteins.
Keywords: gel filtration chromatography